In-depth genetic characterization of the SARS-CoV-2 pandemic in a two-year frame in North Macedonia using second and third generation sequencing technologies - Vukovikj, Maja; Boshevska, Golubinka; Janchevska, Elizabeta; Buzharova, Teodora; Preshova, Ardian; Simova, Milica; Peshnacka, Aneta; Kocinski, Dragan; Kuzmanovska, Gordana; Memeti, Shaban; Gjorgoski, Icko (Frontiers in Virology, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has a persistent negative impact on both the public health and the global economy. To comprehend the origin, transmission routes and discover the mutations that alter the virus’s transmissibility and pathogenicity, full-length SARS-CoV-2 genomes have to be molecularly characterized. Focusing on a two-year time frame (2020-2021), we provide an in-depth virologic and epidemiological overview of the SARS-CoV-2 pandemic in the Republic of North Macedonia by assessing the frequency and distribution of the circulating SARS-CoV-2 variants. Using genetic characterization and phylogenetic analysis we shed light on the molecular evolution of the virus as well as test for a possible connection between specific SARS-CoV-2 haplotypes and the severity of the clinical symptoms. Our results show that one fifth (21.51%) of the tested respiratory samples for SARS-CoV-2 were positive. A noticeable trend in the incidence and severity of the COVID-19 infections was observed in the 60+ age group between males and females. Of the total number of positive cases, the highest incidence of SARS-CoV-2 was noticed in 60+ males (4,170.4/100,000), with a statistically significant (0,0001) difference between the two sexes. Additionally, a 1.8x increase in male mortality and consequentially significantly higher number of death cases was observed compared to females of the same age group (0.001). A total of 327 samples were sequenced in the period March 2020 - August 2021, showing the temporal distribution of SARS-CoV-2 variants circulating in North Macedonia. The phylogenetic analysis showed that most of the viral genomes were closely related and clustered in four distinctive lineages, B.1, B.1.1.7, B.1.351 and B.1.617.2. A statistically significant difference was observed in the 2C_1 haplotype (p=0.0013), where 10.5% of the patients were hospitalized due to severe clinical condition. By employing genetic sequencing, coupled with epidemiological investigations, we investigated viral distribution patterns, identified emerging variants and detected vaccine breakthrough infections. The present work is the first molecular study giving a comprehensive overview of the genetic landscape of circulating SARS-CoV-2 viruses in North Macedonia in a period of two years.